РЕГИОНАЛЬНАЯ СИСТЕМА МОДЕЛЕЙ ФОРМИРОВАНИЯ СТРУКТУРЫ ТОВАРООБОРОТА, ДОХОДОВ И СПРОСА НАСЕЛЕНИЯ НА МЕСТНЫХ РЫНКАХ (Journal of Economic Research & Business Administration, 2015)
Based on the study of living standards and social status of the population of the region defined by the system of models of structure formation of trade, income and consumer demand in local markets.